Effects of Lactococcus lactis subsp. lactis JCM5805 on colonization dynamics of gut microbiota and regulation of immunity in early ontogenetic stages of tilapia. Issue 86 (March 2019) - Xia, Yun; Cao, Jianmeng; Wang, Miao; Lu, Maixin; Chen, Gang; Gao, Fengying; Liu, Zhigang; Zhang, Defeng; Ke, Xiaoli; Yi, Mengmeng
Abstract: The administration of probiotics during early ontogenetic stages can be an effective way to manipulate the gut microbiota of animals. Specifically, the administration of probiotics can enhance gut-colonization success and regulate the immune response. In this study, the effects of early contact with probiotic Lactococcus lactis subsp. lactis JCM5805 on the gut microbial assembly of larvae Nile tilapia were examined. The effects of JCM5805 on IFNα expression through the TLR7 and TLR9-dependent signal transduction pathway as well as larval disease resistance were studied. Three days postfertilization, embryos were randomly allocated into nine 30 L tanks with a concentration of 20 eggs L −1 . Triplicate tanks were performed for each treatment. Treatments included a control group (C), a low probiotic concentration group (T1), where JCM5805 was added to the water at 1 × 10 4 cfu ml −1, and a high probiotic concentration group (T2), where JCM5805 was added to the water at 1 × 10 8 cfu ml −1 . Probiotics were administered continuously for 15 days. qPCR was used to analyze transcript levels of the TLR7, TLR9, MyD88, IRF7 and IFNα genes using RNA extracted from whole embryos on day 5 and 10, and from the intestine of larvae on day 15. Transcription of these genes was also measured in the intestine, liver and spleen of larvae one month after the cessation of probiotic administration. The results showed that MyD88 and IRF7 were significantly elevated on days 5 and 10 in the T2 group. TLR9 and IFNα were also significantly elevated on days 5, 10 and 15 during probiotic application of T2 ( P < 0.05). One month after the cessation of probiotics administration, no significant difference was observed in the expression of these genes ( P > 0.05). The larvae were fed probiotics for 15 days and were infused with Streptococcus agalactiae strain WC1535 at a final concentration of 1 × 10 6 cfu ml −1 . The survival rate of T2 was significantly higher than that of the C group ( P < 0.05). Microbial characterization by Illumina HiSeq sequencing of 16S rRNA gene amplicons showed the significantly higher presence of JCM5805 in the guts of T2 after 15 days of probiotic continuous application. Although JCM5805 was below the detection level after the cessation of probiotic for 5 days, the gut microbiota of the exposed tilapia larvae in T2 remained clearly different from that of the control treatment after the cessation of probiotic administration. These data indicated that a high concentration of the probiotic strain JCM5805 upregulated the expression of IFNα via the TLR7 / TLR9 - Myd88 pathway and enhanced disease resistance of larvae. JCM5805 was only transiently detected and thus was not included in the stable larval microbiota. The early microbial exposure of tilapia larvae affects the gut microbiota at later life stages. However, whether the upregulation of related genes is related to the presence of JCM5805 strain in the intestine requires further verification. Highlights: JCM5805 was used in early ontogenetic stages of tilapia for the first time. JCM5805 upregulated the expression of IFNα via the TLR7 / TLR9 - Myd88 pathway. JCM5805 enhanced disease resistance of tilapia larvae. The early microbial exposure affects the gut microbiota at later life stages. The JCM5805 couldn't colonize in the intestine of tilapia larvae.